Analisis Implementasi Tata Kelola Reklame di Kota Mojokerto - Firdaus, Ananda Dwi; Manggalou, Singgih (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2025)
This study aims to examine the implementation of billboard policy administration in Mojokerto City using a qualitative case study method, analyzed through Edward III's theory. As a part of the strategically located Gerbangkertosusila region, Mojokerto holds considerable economic potential, particularly in the advertising sector. Despite the existence of regulatory frameworks Regional Regulation No. 2 of 2020 and Mayor Regulation No. 9 of 2020 the implementation remains suboptimal, indicated by frequent violations such as unlicensed billboards, which lead to revenue leakage and reduced urban aesthetics. Data were collected through purposive sampling interviews, field observations, and documentation. The study reveals that (1) communication functions relatively well but is hindered by differing interpretations among agencies, limited public understanding, and ineffective strategies; (2) resources are adequate but face obstacles such as manual tools and limited supervisory staff; (3) disposition of implementers is generally effective due to professional commitment, though compliance and supervision still need improvement; and (4) the bureaucratic structure is supported by digital systems and clear regulations, yet faces issues like low taxpayer compliance and overlapping rules. Overall, the implementation of billboard policy in Mojokerto City is not yet optimal and requires significant improvements to increase its effectiveness